Is Pornography Consumption Related to Risky Behaviors During Friends with Benefits Relationships?. Issue 12 (16th October 2020) - Henderson, Elena; Aaron, Sean; Blackhurst, Zachary; Maddock, Meghan; Fincham, Frank; Braithwaite, Scott R.
Abstract: Background: Friends with benefits encounters are a relatively new pattern of relating among emerging adults where risky sexual behavior may occur. Aim: To understand whether pornography consumption is associated with riskier behaviors during friends with benefits encounters. Methods: Cross-sectional study of 2 samples of emerging adults who have engaged in friends with benefits relationships (study 1,  N = 411; study 2,  N = 394). For binary outcomes, we used logistic regression and report odds ratios. For ordinal outcomes, we used ordered logistic regression and reported odds ratios. We tested for moderation by biological sex. Results: Men who consumed pornography more frequently were more likely to engage in risky sexual behaviors during their friends with benefits encounters. More frequent pornography consumption was associated with increased likelihood and amount of intoxication for both the respondent and his partner, less frequent condom use, and a higher probability of having penetrative friends with benefits encounters while intoxicated and not using a condom. For each of these outcomes, our parameter estimates from study 2 fell within the 95% confidence intervals from study 1. These associations persisted when controlling for the effects of binge drinking frequency, broader patterns of problematic alcohol use, trait self-control, openness to experience, and permissive attitudes toward casual sex. The findings of this study may inform interventions to reduce risky behaviors among emerging adults. Limitations: Our cross-sectional studies examined only emerging adults in college with measurement that was exclusively self-reported. Conclusions: These results are discussed in terms of sexual script theory, and several implications for intervention are outlined.